Alternating residence and relocation A view from France - Frédérique Granet (Utrecht Law Review, 2008)
Alternating residence of children is regulated by the Act of 4th March 2002 and is based either on the basis of parental agreement or, if it is impossible, on a judicial decision. Of course, joint physical parental authority implies appropriate material circumstances, but it also refers to the mutual respect of the parents for each other and to their capacity to communicate with each other, thus ensuring that the child is educated and raised in an harmonious environment. However, this type of arrangement for the child can be altered at any time as and when new circumstances arise, for example when of one of the child’s parents moves. The child’s best interests must remain the paramount consideration in establishing, as well as when terminating an alternating residence arrangement.